Efeito de nanopartículas carregadas com sinvastatina na proliferação e ativação de osteoblastos murinos - Braga, Cintia de Melo (2017)
Introduction: The use of polymers as drug nanocarriers offers flexibility in dosage and release kinetics, improving the effectiveness of pharmacological treatments. Simvastatin, a cholesterol-lowering drug, has been shown in some studies to estimate formation. It is believed that this pleiotropic effect and an obtainment of a system for the controlled release can lead to an increase in bone formation. Objective: The purpose of this study was to evaluate the effect of PDLLA polymerase-encapsulated simvastatin (NP-SIN) on the proliferation and activation of murine osteoblasts (OFCOL II) in culture. Methods: The effect of NP-SIN on the viability and proliferation of osteoblasts was investigated through the MTT assay and the ki67 immunostaining, its effect on cell activation for assessed by mineralization assay, measurement of bone alkaline phosphatase levels No culture medium by ELISA, and its protein expression by western blot. The possible mechanisms of action of NP-SIN non-bone metabolism were studied by immunofluorescence and western blot for RANK-L, OPG and BMP-2. Statistical analysis was performed using analysis of variance ANOVA, followed by the Bonferroni test (p <0.05). Results: As nanoparticles were used with uniforms, with approximate diameter of 123 nm, evaluated by transmission electron microscopy. Simvastatin was submitted to a release test, when encapsulated, it was observed progressive and sustained release for up to 6 days, when the degradation process began. Cytotoxic effects on osteoblasts were observed only when incubated with NP-SIN concentrations equal to or greater than 10-1 μM. No increase in osteoblast concentration was observed at any of the concentrations studied. The mineralization assay suggests that NP-SIN (10-2 μM) increases the activity of osteoblasts when compared to controls, not incubated with simvastatin. At the same concentration (NP-SIN 10-2 μM), increased protein expression and alkaline phosphatase release (FA) were associated with a significant increase in the expression of the bone morphogenetic protein (BMP-2). An increase (p <0.05) in the immunoblot of BMP-2 and OPG was also observed. There was no significant difference in RANK-L protein expression between the group of osteoblasts incubated with NP-SIN and the controls. Conclusions: These results indicate a potential beneficial effect of the nanoparticles of PDLLA encapsulated with simvastatin no repair of bone defects through the activation of osteoblasts.